Proteção Dedicada para Redes Ópticas Elásticas Considerando Efeitos de Camada Física - Jr, Jurandir Lacerda; Fontinele, Alexandre; Campelo, Divanilson; Soares, André (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2017)
Elastic Optical Network is a promising technology to compose the Internet infrastructure. For this network it is necessary to provide mechanisms that guarantee its availability even after the occurrence of a failure. It is also important to provide quality of the optical signal, which tends to degrade by the effect of the physical layer impairments. This paper proposes three algorithms that use the dedicated path protection strategy: DP-SNR, DP-BSNR and DP-RQoTO. These algorithms take into account the effects of physical layer impairments in their choices of routes. An evaluation was made with dynamic traffic and requisitions with variable band demands. The three algorithms presented in this paper were compared with other literature proposals, obtaining a reduction in the blocking probability in the order of 90%. Among the proposed algorithms, the DP-RQoTO obtained a decrease in the blocking probability of at least 36% in relation to the DP-SNR and 34% in the DP-BSNR in the EON topology. In the USA topology, the minimum gain of DP-RQoTO was 22% in relation to DP-SNR and 20% in relation to DP-BSNR.